A study on regional differences and convergence of nursing human resource levels in the Yangtze River Economic Belt: an empirical study - Jieting Chen; Yongjin Liu; Yanbo Qu; Juan Xing; Yan Zhu; Xinyue Li; Xiangwei Wu (BMC, 2024)
Abstract Background The Yangtze River Economic Belt, as a core economic region in China, is facing the dual challenges of an aging population and growing healthcare demand, and the balanced development and optimal allocation of nursing human resources is crucial to the region's healthcare system. An in-depth study of the regional differences and convergence of nursing human resources in the region will provide a key basis for policy makers to achieve equity and efficiency in healthcare services and meet the growing demand for healthcare. Aim To analyze the regional differences and convergence characteristics of nursing human resource levels in the Yangtze River Economic Belt, and to provide scientific references for optimizing regional nursing human resource allocation. Methods Based on the panel data of 107 cities in the Yangtze River Economic Belt from 2010 to 2020, the regional differences and their sources were analyzed by using Dagum's Gini coefficient, and the convergence characteristics were examined by the coefficient of variation and spatial convergence model. Results The average value of the number of nursing human resources in the Yangtze River Economic Belt is 2,132,300 people, with obvious regional differences, and the hypervariable density difference (53.01%) is the main source of the regional differences; there are obvious trends of σ-convergence and conditional β-convergence of the level of nursing human resources in the overall and the three major regions of the upstream, midstream, and downstream, and different factors have different moderating effects on the speed of spatial convergence in the other areas. Conclusion The implementation of precise policies for nursing human resources in different regions of the Yangtze River Economic Belt steadily reduces the regional differences between the upper, middle, and lower reaches and enhances the spatial linkage between regions of nursing human resources to improve the quality of nursing human resources.